Para que serve o passado: cronache di poveri amanti e a crônica da história - Betella, Gabriela Kvacek [UNESP] (My University, 2012)
Vasco Pratolini recreates the 1920’s and the assertion of fascism resorting to the medieval and historiographical tradition, to the social outlook and the childhood memoir. Under the effects of the intellectual movement of the Italian Resistance, within the democratic context of the parliamentary republic and pluripartyism (1946- 1948), the novel makes clear the equalitarian perspective betraying the represented moment, when hopelessness crowned the political and social life. Carlo Lizzani shoots his adaptation in the closure of horizons caused by the restoration of the conservative forces (1953), reducing the visionary focus of the narrative and representing the past from the disillusionments of the present.

Vasco Pratolini recria os anos de 1920 e a afirmação do fascismo recorrendo à tradição medieval e historiográfica, ao olhar social e à memória de infância. Sob os efeitos do movimento intelectual da Resistência italiana, no contexto democrático da república parlamentar e do pluripartidarismo (1946-1948), o romance evidencia a perspectiva igualitária traindo o momento representado, quando a desesperança coroava a vida política e social. Carlo Lizzani filma sua adaptação no fechamento dos horizontes com a restauração de forças conservadoras (1953), diminuindo o foco visionário da narrativa e representando o passado a partir das desilusões do presente.
What the past is for: cronache di poveri amanti and the chronicle of history
Keywords: Literature and cinema; Vasco Pratolini; Carlo Lizzani; Literatura e cinema; Vasco Pratolini; Carlo Lizzani